THE COMPARISON OF THE SELECTED METHODS FOR DETERMINING THE SIZE OF THE SAFETY STOCK AND THEIR APPLICATION IN THE FOOD INDUSTRY (Perner's Contacts, 2016)
The problem of inventory management solves many businesses every day. This is mainly due to two conflicting trends. Both companies are striving to satisfy their customers, but on the other hand, they want to eliminate the amount of capital tied up in inventories. Safety stock can capture the three basic types of imbalances – on the input, output and consumption. The correct size setting of safety stock influences the economics of enterprise and customer satisfaction. This article compares the selected method for determining the size of the safety stock and applied in practice in the food industry environment.
Keywords: safety stock; food industry; inventory management; bullwhip effect